Solid State Production Of Halophilic Lipase By Halophilic/Halotolerant Fungi Using Various Agricultural Waste Substrates - Sharifah Sabirah Syed Hamzah (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Lipases are well known among the extensively used biocatalysts, because they have the ability to catalyze several remarkable reactions in aqueous and non-aqueous media like esterification and transesterification. The present study explores the production of halophilic lipase by FIMT1 under solid-state fermentation (SSF). Three isolated fungi (FIMT1, FSL5 and FSL6) were obtained from and cultured using agar medium. These fungi were supplemented with different agricultural wastes substrates together with olive oil to determine the best possible production medium for optimal halophilic lipase production. Olive oil was being used to enhance the production of halophilic lipase. FIMT1 showed highest halophilic lipase activity on empty fruit bunch (EFB) as the substrate while the lowest lipase activity was recorded on FIMT1 with wheat bran as the substrate. The most favourable pH and temperature for halophilic lipase production by FIMT1 were 8.0 at 60 C after 7 days of incubation period. Besides, enzymatic production increased when the organism was cultured in medium augmented with sucrose as a source of Carbon and sodium nitrate and olive oil as sources of Nitrogen and fat respectively. The result of this study revealed that lipase activity (0.3720 (So(BM/min) increased from 0.1306 (So(BM/min. FIMT1 could be considered as a potential source of extracellular lipase production under alkaline environment..